Distributed Electro-Mechanical Coupling Effects in a Dielectric Elastomer Membrane Array - Neu, J.; Croce, S.; Willian, T.; Hubertus, J.; Schultes, G.; Seelecke, S.; Rizzello, G. (Experimental mechanics, 2023)
Background Dielectric elastomer (DE) transducers permit to effectively develop large-deformation, energy-efficient, and compliant mechatronic devices. By arranging many DE elements in an array-like configuration, a soft actuator/sensor system capable of cooperative features can be obtained. When many DE elements are densely packed onto a common elastic membrane, spatial coupling effects introduce electro-mechanical interactions among neighbors, which strongly affect the system actuation and sensing performance. To effectively design cooperative DE systems, those coupling effects must be systematically characterized and understood first. Objective As a first step towards the development of complex cooperative DE systems, in this work we present a systematic characterization of the spatial electro-mechanical interactions in a 1-by-3 array of silicone DEs. More specifically, we investigate how the force and capacitance characteristics of each DE in the array change when its neighbors are subject to different types of mechanical or electrical loads. Force and capacitance are chosen for this investigation, since those quantities are directly tied to the DE actuation and sensing behaviors, respectively. Methods An electro-mechanical characterization procedure is implemented through a novel experimental setup, which is specifically developed for testing soft DE arrays. The setup allows to investigate how the force and capacitance characteristics of each DE are affected by static deformations and/or electrical voltages applied to its nearby elements. Different combinations of electro-mechanical loads and DE neighbors are considered in an extensive experimental campaign. Results The conducted investigation shows the existence of strong electro-mechanical coupling effects among the different array elements. The interaction intensity depends on multiple parameters, such as the distance between active DEs or the amount of deformation/voltage applied to the neighbors, and provides essential information for the design of array actuators. In some cases, such coupling effects may lead to changes in force up to 9% compared to the reference configuration. A further coupling is also observed in the DE capacitive response, and opens up the possibility of implementing advanced and/or distributed self-sensing strategies in future applications. Conclusion By means of the conducted experiments, we clearly show that the actuation and sensing characteristics of each DE in the array are strongly influenced by the electro-mechanical loading state of its neighbors. The coupling effects may significantly affect the overall cooperative system performance, if not properly accounted for during the design. In future works, the obtained results will allow developing cooperative DE systems which are robust to, and possibly take advantage of, such spatial coupling effects.